Myelin injury without astrocytopathy in neuroinflammatory disorders with MOG antibodies. - Kaneko, K; Sato, D; Nakashima, I; Nishiyama, S; Tanaka, S; Marignier, R; Hyun, J; Oliveira, L; Reindl, M; Seifert-Held, T; Sepulveda, M; Siritho, S; et al. (BMJ Publishing Group, 2016)
Objective To compare myelin and astrocyte injury in patients with antibodies against myelin oligodendrocyte glycoprotein (anti-MOG) or aquaporin-4 (anti-AQP4), and multiple sclerosis (MS). Methods Myelin basic protein (MBP) and glial fibrillary acidic protein (GFAP) levels were measured in the cerebral spinal fluid (CSF) from anti-MOG+ or anti-AQP4+ patients tested in both sera and CSF by cell-based assays with live transfected cells. Results In total, 75.6% (68/90) of the patients were positive for either anti-MOG or anti-AQP4 antibodies in both serum and CSF; 74.2% (23/31) were anti-MOG+, and 76.3% (45/59) were anti-AQP4+. No patients were only CSF positive or were positive for both anti-MOG and anti-AQP4 antibodies, and none of the MS patients or controls had these autoantibodies in the serum or CSF. MBP levels were elevated in the anti-MOG+ cases compared to the multiple sclerosis (MS) patients, and the levels found were similar between anti-MOG+ cases and anti-AQP4+ neuromyelitis optica spectrum disorder (NMOSD) cases. Meanwhile, GFAP was only elevated in the anti-AQP4+ NMOSD. Moreover, CSF pleocytosis, high protein levels, and oligoclonal IgG band negativity distinguished the anti-MOG+ cases from MS patients. Conclusions Myelin injury was more severe in the anti-MOG+ cases than in the MS cases, and anti-MOG+ cases have differences in the CSF characteristics compared to MS. GFAP elevation in anti-AQP4+ cases was absent in anti-MOG+ patients (even in cases with NMOSD phenotype), indicating that immune-mediated astrocytopathy is unique to anti-AQP4+ patients. Our study suggests that anti-MOG+ cases are distinct from MS and anti-AQP4+ NMOSD.